Analysis Of The Factors That Influence The Achievement Of K1 In The Working Area at The Tirtoyudo Community Health Center - Andariningsih Andariningsih (Journal for Quality in Public Health, 2020)
The problem of maternal death is still a major problem in the health sector. The health of a pregnant women is an important aspect to consider in a women’s life cycle because during her pregnancy there can be unexpected complications. Pregnancy checks should be done as early as possible, as soon as a woman feels she is pregnant. The purpose of the study was to determine the effect of partial and silmutan between the pregnant women’s knowledge, husbands support, and the role of cadres on the level of achievement of K1 in the work area at the health center of Tirtoyudo. The research design used is quantitative research using “explanatory research. The sampling technique used is “proportional sampling” of 105 respondents. This study uses a survey method using a questionnaire that contains statements and the collection of dats by interview and questionnaire, then in the measurement technique of research data using a Likert scale. Likert scale has a gradation from very positive to very negative to four levels. Instruments that both must meet two requirements is important is valid and reliable. Validity is the level of reliability and validity of the tool measuring are used, while the test of reliability is useful to establish whether the instrument, in terms of this questionnaire, can be used more than one time, at least not by the respondents are the same and will generate data consistent. Results The study showed that 1) the knowledge Ibu Hamil has the effect of the positive and signiikan against keputusanIbu Pregnant To do Visits First (K1) three months of the first period of pregnancy , 2) support of husband does not have the effect that is significant to the decision of the mother pregnant to do the visit first (K1) three months of the first period of pregnancy and 3) the role of the CadreHealth has the effect that a positive and significant to the decision of the mother pregnant to do the visit first (K1) three months of the first period of pregnancy